Storage of Encapsulated Liver Cell Spheroids at â€“80Â°C after Storage at Liquid Nitrogen Temperatures - Kilbride, Peter; Selden, Clare; Fuller, Barry; Morris, John (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A